Functional analysis of the seven in absentia ubiquitin ligase family in tomato. (29th January 2018) - Wang, Wenjie; Fan, Youhong; Niu, Xiangli; Miao, Min; Kud, Joanna; Zhou, Bangjun; Zeng, Lirong; Liu, Yongsheng; Xiao, Fangming
Abstract: Seven in absentia (SINA) protein is one subgroup of ubiquitin ligases possessing an N‐terminal cysteine‐rich really interesting new gene (RING) domain, two zinc‐finger motifs, and a C‐terminal domain responsible for substrate‐binding and dimerization. In tomato ( Solanum lycopersicum ), the SINA gene family has six members, and we characterize in this study all tomato SINA ( SlSINA ) genes and the gene products. Our results show that SlSINA genes are differentially regulated in leaf, bud, stem, flower, and root. All SlSINA proteins possess RING‐dependent E3 ubiquitin ligase activity, exhibiting similar specificity towards the E2 ubiquitin‐conjugating enzyme. SlSINA1/3/4/5/6 are localized in both cytoplasm and nucleus, whereas SlSINA2 is exclusively localized in the nucleus. Moreover, all SlSINAs can interact with each other for homo‐ or hetero‐dimerization. The functionality of SlSINA proteins has been investigated. SlSINA4 plays a positive role in defense signalling, as manifested by elicitation of E3‐dependent hypersensitive response‐like cell death; the other SlSINAs are negative regulator and capable to suppress hypersensitive response cell death. Transgenic tomato plants overexpressing SlSINA2 exhibit pale‐green leaf phenotype, suggesting SlSINA2 regulates chlorophyll level in plant cells, whereas transgenic tomato plants overexpressing SlSINA5 have altered floral structure with exserted stigma, implicating SlSINA5 plays a role in flower development. Abstract : Our results suggest all SlSINA proteins are involved in regulation of defense signaling. In addition, SlSINA2 regulates chlorophyll level in leaf tissues, whereas SlSINA5 plays a role in flower development.